Efeito da administração da sulpirida no desenvolvimento folicular em éguas - Cruz, Fernando Dal Sasso Mendonça [UNESP] (2014)
The induction of multiple ovulations in domestic species is of extreme importance to provide improvements of results and costs of biotechnologies such as embryo transfer, artificial insemination with poor quality semen, oocyte transfer among others. This study aimed to determine if sulpiride could induce multiple ovulations in mares. Seventeen mares randomly passed the two experimental groups. In the group of mares treated with sulpiride 1mg/kg (IM) every 12 hours, the protocol was initiated only in mares that have achieved a follicle of 24 mm ± 2 mm in diameter and a second follicle ≥ 20 ± 2 mm in diameter. In the control group, were used the same protocol, but the mares were treated with 0.9% saline solution (IM) every 12 hours. During the ultrasound evaluation if was observed the follicular growth the treatment even when the lower follicle reached at least 33 mm in diameter. At this time the ovulation was induced with 1500 IU of hCG. Artificial insemination was performed 24 hours after ovulation induction, and the embryos were collected on the eighth day after the first ovulation. The variables were analyzed using Student's t Fisher's exact test and test. In group treated, 35% of the mares had more than one ovulation and ovulation an average of 1.4 per cycle while in control group only 11% of the mares had more than one ovulation and ovulation an average of 1.1 per cycle. In the group treated with sulpiride the time of the treatment beginning to the first ovulation was 3,9 ± 0.9 days whereas the control group was 4.9 ± 1.0 (P<0,001). Administration of Sulpiride during follicular development stimulated ovarian activity but did not contribute to a significant increase in the rates of double or triple ovulations, however some mares had a higher incidence of multiple ovulations when subjected to the proposed protocol, suggesting that further studies should be conducted for clarification of these results